2014
DOI: 10.1021/jp410457z
|View full text |Cite
|
Sign up to set email alerts
|

DNA Strand Elongation Induced by Small Gold Nanoparticles at High Ethanol Content

Abstract: Small N-(2-mercaptopropionyl)glycine gold nanoparticles (AuNPs) of 1.6 nm core size were synthesized. The mode of binding and the effect of ethanol on DNA conformational changes induced by AuNPs nanoparticles were studied in detail by means of fluorescence and circular dichroism (CD) spectroscopy, zeta potential, dynamic light scattering (DLS), viscometric, and atomic force microscopy (AFM) methods. The measurements were done at different molar ratios R = C AuNPs /C DNA and at different ethanol content. Both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Moreover, under suitable R values (R=C AuNPs /C DNA ) and ethanol contents, the CD spectra, dynamic light scattering and atomic force microscopy experiments revealed that AuNPs induced the formation of a rather compact AuNPs/DNA complex. The results suggested that this form is a coiled DNA structure stabilized by AuNPs interconnections . For small, citrate‐capped gold NPs (5 nm), the denaturation of the helix occurs to form the previously mentioned complex ssDNA‐AuNP (Figure and ) …”
Section: Interactions Between Aunps and Oligonucleotidesmentioning
confidence: 74%
See 1 more Smart Citation
“…Moreover, under suitable R values (R=C AuNPs /C DNA ) and ethanol contents, the CD spectra, dynamic light scattering and atomic force microscopy experiments revealed that AuNPs induced the formation of a rather compact AuNPs/DNA complex. The results suggested that this form is a coiled DNA structure stabilized by AuNPs interconnections . For small, citrate‐capped gold NPs (5 nm), the denaturation of the helix occurs to form the previously mentioned complex ssDNA‐AuNP (Figure and ) …”
Section: Interactions Between Aunps and Oligonucleotidesmentioning
confidence: 74%
“…The results suggestedt hat this form is ac oiled DNA structure stabilized by AuNPs interconnections. [95] For small, citrate-capped gold NPs (5 nm), the denaturation of the helix occurs to form the previously mentioned complex ssDNA-AuNP (Figure 10 and1 4). [44] Figure 14 shows the evolution of the absorbance intensity at 260 nm with varying temperatures and at differentD NA/AuNP ratios, showingadecay of absorbance intensity with increasing NP concentrations.…”
Section: Interactions Of Dsdna With Aunpsmentioning
confidence: 82%
“…The collapse process by which extended polynucleotide chains modify their structures into compact particles is called condensation, which is a common process for native genomes. 5 The controlled DNA condensation has been demonstrated to be possible with a variety of reagents such as enzymes, 6 multivalent ions, 7,8 alcohols, 9,10 polyamines, 11 metal complexes, 12 nanoparticles, 13 and cationic surfactants. [14][15][16][17][18] In this regard, the gemini surfactants have received a lot of attention recently due to its unique physicochemical properties, low cytotoxicity and potential bactericidal properties.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the magnitude of the measured zeta potential is an indication of the repulsive force that is present and can be used to predict the long-term stability of the nanoparticle. Naturally, it also allows us to obtain information about the proximity of ligands that could neutralize the surface of charged nanoparticles [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%